The Partisan Brain: An Identity-Based Model of Political Belief. Issue 3 (March 2018) - Van Bavel, Jay J.; Pereira, Andrea
Abstract : Democracies assume accurate knowledge by the populace, but the human attraction to fake and untrustworthy news poses a serious problem for healthy democratic functioning. We articulate why and how identification with political parties – known as partisanship – can bias information processing in the human brain. There is extensive evidence that people engage in motivated political reasoning, but recent research suggests that partisanship can alter memory, implicit evaluation, and even perceptual judgments. We propose an identity-based model of belief for understanding the influence of partisanship on these cognitive processes. This framework helps to explain why people place party loyalty over policy, and even over truth. Finally, we discuss strategies for de-biasing information processing to help to create a shared reality across partisan divides. Highlights: Over 2 billion people use social media every day, and many use it to read and discuss politics. Social media also facilitate the spread of fake news and hyper-partisan content. Online discussions of politicized topics, including political events and issues (e.g., same-sex marriage, climate change, gun control), resemble an echo chamber. That is, posts on these topics are shared primarily by people with similar ideological preferences. Political polarization is most likely when users employ moral/emotional language. This may reflect ideological differences between people on the left versus right or partisanship. Online partisan criticism that derogates political opponents increases political polarization. Liberals are somewhat more likely to share cross-ideological content on social media (i.e., information posted by people with different ideological beliefs).